2022
DOI: 10.1101/2022.11.10.516003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammation in the tumor-adjacent lung as a predictor of clinical outcome in lung adenocarcinoma

Abstract: Early-stage lung adenocarcinoma is typically treated by surgical resection of the tumor. While in the majority of cases surgery can lead to cure, approximately 30% of patients progress. Despite intense efforts to map the genetic landscape of early-stage lung tumors, there has been limited success in discovering accurate biomarkers that can predict clinical outcomes. Meanwhile, the role of the tumor-adjacent tissue in cancer progression has been largely ignored. To test whether tumor-adjacent tissue can be info… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…2.3 | Single-nuclei RNA sequencing (snRNA-seq) analysis GSE229253 (Dolgalev et al, 2023) validated hub gene expression, excluding genes with fewer than 200 detected genes. Details are in the Appendix S1.…”
Section: Wgcnamentioning
confidence: 99%
“…2.3 | Single-nuclei RNA sequencing (snRNA-seq) analysis GSE229253 (Dolgalev et al, 2023) validated hub gene expression, excluding genes with fewer than 200 detected genes. Details are in the Appendix S1.…”
Section: Wgcnamentioning
confidence: 99%
“…Studies evaluating gene and protein expression in adenocarcinoma have shown no significant association with specific histologic patterns, 41,42 that is, there is no gene/ protein signature for individual histologic patterns. It has been shown however that histologic patterns are associated with distance from stem cell differentiation: lepidic pattern is closer to differentiated pulmonary epithelium, whereas highgrade histologic patterns are closer to stem cells, 43 thus confirming an association of patterns with differentiation.…”
Section: Correlation Between Histologic Grade Molecular Alterations G...mentioning
confidence: 99%
“…The discoveries add to a more profound comprehension of the growth microenvironment and its effect on clinical results. Elena-Georgiana Dobre et al [ 24] give an exhaustive outline of imaging methods in skin malignant growth pathobiology. The review accentuates the capability of cutting edge imaging advancements for further developed conclusion and observation in clinical companions.…”
Section: Related Workmentioning
confidence: 99%